Respostas

2013-12-16T09:59:12-02:00
A) (3+x)²                 b)(x+5)²                   c) (x+y)²                 d)(x+2)²
(3+x).(3+x)             (x+5).(x+5)              (x+y).(x+y)              (x+2).(x+2)
9+3x+3x+x²            x²+5x+5x+25          x²+xy+xy+y²           x²+2x+2x+4
9+6x+x²                 x²+10x+25                                            x²+4x+4

e) 
(3x+2)²
(3x+2).(3x+2)
9x²+6x+6x+4
9x²+12x+4
1 5 1
2013-12-16T10:33:10-02:00
(a+b)^{2}=a^{2}+2ab+b^{2}

a) (3+x)^{2}=9+6x+x^{2}
b) (x+5)^{2}=x^{2}+10x+25
c) (x+y)^{2}= x^{2}+2xy+y^{2}
d) (x+2)^{2}=x^{2}+4x+4
e) (3x+2)^{2}=9x^{2}+12x+4